Musculoskeletal physical therapy after COVID-19: Time for a new "normal" - Lewis, J.; Mc Auliffe, S.; O'Sullivan, K.; O'Sullivan, P.; Whiteley, R. (Journal of Orthopaedic & Sports Physical Therapy, 2021)
In late 2019, a previously unknown coronavirus, SARS-CoV-2 (the coronavirus that causes COVID-19), was reported in Wuhan, China. Similar to the polio virus epidemic, the fear, uncertainty, and collective response associated with COVID-19 have disrupted daily life on a global scale. In this editorial, we argue that it is time for musculoskeletal physical therapists to grasp the opportunity provided by the COVID-19 pandemic to provide care that is (1) primarily active, (2) focused on self-efficacy and self-management, and (3) far less reliant on passive therapies.